Albertine Deletaille (1902-2008) : illustratrice et pédagogue de la petite enfance - Sylvain Wagnon (Strenae)
Albertine Deletaille (1902-2008) was a prolific author and illustrator, with more than 35 books in the Père Castor series. She wrote some of the collection’s “classics”, including Chat lune and Blancheline. Through a study of previously unpublished archives, we will examine her aesthetic influences, the way she conceived the creation of a book for young people, and above all the educational concepts and vision of the child that are reflected in her work. The aim is to get to know and understand the work of this Belgian author and illustrator of Père Castor children’s books by exploring her human and intellectual journey.